Edge of the world [videorecording (DVD)] - Haussman, Michael; Rhys-Meyers, Jonathan, 1977-; Monaghan, Dominic, 1976-; Ho, Josie, 1974- (Samuel Goldwyn Films, 2021)
The epic true story of Sir James Brooke, the British adventurer who became King of Sarawak in the 1840's and embarked on a lifelong crusade to end piracy and head-hunting - only to face charges of murder and piracy himself. In 1839, Brooke flees Victorian England to explore Borneo. After a pirate attack, Brooke allies with rival princes to seize a rebel fort. To save prisoners from beheading, Brooke agrees to be crowned Rajah. James begs the Royal Navy for a steamship to fight pirates, but the British want his kingdom as a colony. Makota's pirates massacre Brooke's capital, leaving James half-dead. To save his people, he must shed Englishness and embrace the jungle: "All of it, the beauty and the blood."